Development of Media Puzzle Using Game Based Learning Approach to Improve Learning Outcomes Student Mathematics in Elementary School - Riskyka; Lubis, Renni Ramadhani; Yusnita, Novi Cynthia (Berpusi Publishing, 2023)
This study aims to develop media puzzles with a game based learning approach to improve students' mathematics learning outcomes in elementary schools. This research is a research and development (RnD) research, using a 4-D development model, including: 1) define, 2) design, 3) develop and 4) disseminate. The subjects of this study were 25 grade IV students consisting of 9 male students and 16 female students. The research object is puzzle media with a game based learning approach. Data collection techniques are observation, questionnaires, and tests. Based on the validation results of the puzzle media with the game based learning approach, it shows that: (1) the level of validity of the puzzle media with the game based learning approach gets an average score from material and media experts of 4.29 and 4, 17 with the categories